2001
DOI: 10.1007/s003300101115
|View full text |Cite
|
Sign up to set email alerts
|

MR imaging of the vessel wall

Abstract: Since the risks for thrombosis are more dependent on plaque composition than on the degree of luminal narrowing, the radiological assessment of atherosclerosis should extend beyond mere depiction of the arterial lumen. High-resolution MRI of the vessel wall can provide important information about the individual makeup of atherosclerotic plaques, potentially enabling early detection and characterization of lesions before narrowing of the vessel lumen occurs. The MR-based assessment of the vessel wall with suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 53 publications
0
23
0
5
Order By: Relevance
“…Along with recent advances in imaging devices and techniques, many studies have documented the usefulness of high-resolution MR imaging in the diagnosis of plaque. [14][15][16][17][18][19][20][21] In addition to sorting plaque composition on the basis of MR signal intensity, if soft plaque can be differentiated from nonsoft plaque by overall plaque MR signal intensity, MR imaging will be a simple, objective, and useful method to diagnose carotid atherosclerosis. To our knowledge, however, few studies have closely assessed the MR imaging signals of plaque components by comparing CEA specimens with carotid MR imaging in vivo, 22 and the findings on MR imaging of carotid soft plaque have not been described.…”
mentioning
confidence: 99%
“…Along with recent advances in imaging devices and techniques, many studies have documented the usefulness of high-resolution MR imaging in the diagnosis of plaque. [14][15][16][17][18][19][20][21] In addition to sorting plaque composition on the basis of MR signal intensity, if soft plaque can be differentiated from nonsoft plaque by overall plaque MR signal intensity, MR imaging will be a simple, objective, and useful method to diagnose carotid atherosclerosis. To our knowledge, however, few studies have closely assessed the MR imaging signals of plaque components by comparing CEA specimens with carotid MR imaging in vivo, 22 and the findings on MR imaging of carotid soft plaque have not been described.…”
mentioning
confidence: 99%
“…Plaque imaging and composition assessment at high resolution in the carotid arteries demands a high SNR and, therefore, optimal coil/signal reception (2,4,5,9,10). Previous studies demonstrated that phased-array coils provide better SNR than single-loop surface coils (6,11,12).…”
Section: Discussionmentioning
confidence: 99%
“…MRI HAS THE POTENTIAL to define atherosclerotic plaque components in vivo at the carotid artery (1)(2)(3)(4)(5)(6). Normally, the atherosclerotic plaque in the carotid artery has an averaged length of 2.0 -2.5 cm and the thickness in the axial plane is 5-10 mm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance imaging (MRI) can be used to diagnose and stage blood vessel disease by identifying lumen narrowing in a stenosis, by measuring blood flow, and by imaging plaque in the arterial wall 1 . We are focusing on the latter application in a comprehensive program that includes new imaging technologies such as intravascular coils, high field MRI, imaging agents, and advanced computer image analysis.…”
Section: Introductionmentioning
confidence: 99%